INFLUENCE FACTORS OF CONTACT PRESSURE BETWEEN SHRINK-FIT TOOL HOLDER AND SHANK - LIU Bo; ZHOU HouMing; ZHOU YouHang; ZHANG GaoFeng; PENG RuiTao (Jixie qiangdu)
To improve the contact state of shrink-fit tool holder and shank,the factors affecting the contact pressure distribution in matching surface are discussed. The shrink-fit tool holder and shank parametric model is established by ANSYS parametric design language commend stream. The pressure distribution on the matching surface is revealed by pressure sensitive films. Compared with the finite element analysis,the reliability of parametric model is verified. The contact pressure is calculated by getting the stress distribution of the matching surface on the holder. Calculations indicated that the average pressure,max pressure and uniformity on matching surface will decrease with the increase of holder thickness,inner diameter,length and angle of matching,but the trend and range of the pressure distribution are the same; increased the thickness of the shank and selecting the thickness of the shrink-fit tool holder properly is helpful to reduce the stress concentration.